Gulfization of the Arab World - Jones, Marc Owen; Porter, Ross; Valeri, Marc (Exeter critical Gulf series, 2018)
This volume discusses the notion of Gulfization, and examines how thoughts, ideologies, way of life and practises are transmitted, changed, and transduced inside and outside the Gulf. From historical perspectives such as the impact of the 1952 Egyptian Revolution in Yemen, to studies on the contemporary projection of Salafism or hyper-nationalism in the Gulf monarchies, this book explores, contends, and critiques the transnational and regional currents that are making, and unmaking, the new Gulf Moment.